2005
DOI: 10.1111/j.1365-2745.2005.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed mass, seedling size and neotropical tree seedling establishment

Abstract: Summary 1We examined among-and within-species effects of seed mass for seedling establishment from seed to 5 years of age in a field experiment at Paracou, French Guiana. 2 Six seeds of each of eight species were weighed and planted into each of 120 plots (1 m 2 ) throughout closed-canopy forest along 12 100-m transects in 1998. 3 We described the microhabitat of each planting site using principal components derived from measurements of light availability, soil moisture, carbon and nitrogen content, and soil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
150
2
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 69 publications
14
150
2
12
Order By: Relevance
“…This would explain why leaves of seedlings of Q. petraea from bigger seeds were more enriched in the isotope C than those from smaller seeds at the end of the first year. The fact that such link was not observed for Q. pyrenaica suggests a different pattern of mobilization/allocation of seed carbon compounds to leaves between species (see Baraloto et al 2005). Taking into account the higher allocation of biomass to roots in Q. pyrenaica and its typical sprouting habit relative to Q. petraea (RodriguezCalcerrada et al 2008), seed carbohydrates could be preferentially moved from the seeds to the roots in the former species.…”
Section: Controls Of First-year Vertical Growthmentioning
confidence: 99%
“…This would explain why leaves of seedlings of Q. petraea from bigger seeds were more enriched in the isotope C than those from smaller seeds at the end of the first year. The fact that such link was not observed for Q. pyrenaica suggests a different pattern of mobilization/allocation of seed carbon compounds to leaves between species (see Baraloto et al 2005). Taking into account the higher allocation of biomass to roots in Q. pyrenaica and its typical sprouting habit relative to Q. petraea (RodriguezCalcerrada et al 2008), seed carbohydrates could be preferentially moved from the seeds to the roots in the former species.…”
Section: Controls Of First-year Vertical Growthmentioning
confidence: 99%
“…Several studies showed that individuals of species with larger seeds have higher chances of surviving initial developmental stages than those with smaller seeds, mainly when growing under stressful conditions such as low light, high herbivory rates and low nutrient availability within the soil (Leishman 2001;Moles & Westoby 2004;Baraloto et al 2005;St-Denis et al 2013). Further, Pereira et al (2013), carried out an experiment including seven tree species from Brazilian Savanna which was monitored along 24 months in the fi eld, and found that species with small seeds (smaller than 50 mg) were more vulnerable to competition with exotic grasses than individuals of species with larger seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Pereira et al (2013), carried out an experiment including seven tree species from Brazilian Savanna which was monitored along 24 months in the fi eld, and found that species with small seeds (smaller than 50 mg) were more vulnerable to competition with exotic grasses than individuals of species with larger seeds. However, most studies evaluated the relationship between seed mass and survival in direct sowing experiments (Camargo et al 2002;Baraloto et al 2005;Pereira et al 2013;St-Denis et al 2013). Moles & Westoby (2004) found that seed mass did not influence the probability of transition from viable seed to newly emerged seedlings of 33 species; however, this trait had a strong effect on the probability of plant survival after the first weeks of emergence.…”
Section: Introductionmentioning
confidence: 99%
“…Seed predators are important selection agents acting on seed size because they are likely to select the most profitable seeds (Moegenburg, 1996;Brewer, 2001). Seed mass can have substantial effects on seed survival according to the different threats to which they are exposed in the course of their development, dispersal, and establishment as seedlings (Baraloto et al, 2005). Larger seeds may experience shorter dispersal distances (Howe et al, 1985), their production per individual is often comparatively reduced (Jakobsson and Eriksson, 2000), and they result in competitive seedlings (Turnbull et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In extremes of size spectrum, nuts may present at least two-fold difference in size. Multiple factors may favor large seeds (Baraloto et al, 2005), and, among them, might be an enhanced potential to swamp seed predators as yet tested for seed cotyledons (Harms and Dalling, 1997;Mack, 1998). Then, palms producing moderate number of larger nuts might swamp rodents, as those ones with increased production of small fruits.…”
Section: Introductionmentioning
confidence: 99%